Walking toward peace : the true story of a brave woman called Peace Pilgrim - Krull, Kathleen (Flyaway Books, 2021)
"Tells the true story of Peace Pilgrim, a female activist and spiritual leader who sacrificed everything to travel by foot around America promoting peace"--